Religious Tolerance in the ‘Hajat Sasih’ Tradition of Kampung Naga: An Ethnographic Perspective - Tonny Ilham Prayogo; Muttaqin Muttaqin; Alhafidh Nasution; Muhammad Nurrosyid Huda Setiawan; Nurazizah Jamilah (Fenomena, 2025)
The phenomenon of religious intolerance has recently become increasingly intractable and complex. Some records indicate that secondary-level institutions, state universities, and religious education institutions within communities are susceptible to radical ideologies. This research project aims to analyse the role of local wisdom, exemplified by the Hajat Sasih tradition observed by the Kampung Naga community, in fostering tolerance. The research method applied is quasi-qualitative, focusing on understanding the nature of tolerance and its implications for the formation of interfaith harmony in relation to the Hajat Sasih culture in Kampung Naga. To ensure the accuracy and reliability of the data, meticulous observation and in-depth interviews were employed as data collection techniques. The findings of this study can be summarised as follows: first, the community views the Hajat Sasih culture as a means of respecting and appreciating local wisdom. Second, the tolerance model applied is through the symbolism and meaning of the Hajat Sasih ceremony. Third, education in Kampung Naga facilitates the community's openness to external or foreign cultures while maintaining local customs. Fenomena intoleransi dalam beragama belakangan ini semakin menguat dan kompleksitas. Beberapa catatan telah diungkapkan bahwa lembaga jenjang menengah dan perguruan tinggi negeri serta lembaga pendidikan keagamaan di masyarakat terpapar paham radikalimse. Penelitian ini bertujuan untuk menganalisa dan menguatkan sikap toleransi yang dilakukan oleh kearifan lokal yakni masyarakat Kampung Naga melalui tradisi Hajat Sasih. Metode penelitian yang dilakukan oleh peneliti yakni kuasi kualitatif yang berfokus pada pemahaman toleransi dan implikasinya dalam pembentukan harmoni antar umat beragama dengan Kebudayaan Hajat Sasih di Kampung Naga. Teknik pengumpulan data yang diterapkan pada penelitian ini adalah observasi terhadap objek dengan hati-hati (meticulous observation) dan wawancara mendalam (in depth interview) yang digunakan untuk mendapatkan informasi yang akurat dari informan atau narasumber. Hasil temuan dalam penelitian ini yakni pertama, pandangan masyarakat terhadap budaya Hajat Sasih adalah menghormati dan menghargai adat kearifan lokal yang telah dijalankan oleh para sesepuh/leluhur. Kedua, model toleransi yang diterapkan yakni melalui simbolisasi dan makna upacara Hajat Sasih. Ketiga, peran pendidikan di Kampung Naga yang merealisasikan keterbukaannya terhadap dunia luar atau budaya asing dengan mempertahankan adat lokalnya.